Tapecomys primus (Rodentia: Cricetidae), nuevo género y especie para la Argentina - Barquez, Ruben Marcos (2006)
A new genus and species of a sigmodontine rodent is added to the mammals fauna of Argentina. Tapecomys primus was previously known only for two specimens collected at the type locality in Bolivia. Another specimen, reported here, was captured in a region of the Yungas forests of Jujuy province. This represents the third known specimen up to now for the species and the first for Argentina. Description of the specimen as well as a comparison with those from Bolivia is provided.